COPING BEHAVIOR IN TARKINGTON’S 'THE MAGNIFICENT AMBERSONS': AN INDIVIDUAL PSYCHOLOGICAL APPROACH - Radityo Tri Nugroho; Afifah Linda Sari (Leksema: Jurnal Bahasa dan Sastra, 2020)
The object of the research is a novel the magnificent Ambersons by Newton Booth Tarkington. The problem of this study is how George Amberson Minafer, the major character copes with his problem. The objective of this study is to analyze the novel based on the psychological approach. The researcher employs a qualitative method. In this method, the researcher uses two data sources, namely primary and secondary data sources. The primary data source is the novel itself. The secondary data sources are books about psychology and other sources, which are related to the analysis. The method of data collection is documentation and the technique of data analysis is descriptive technique. Based on the analysis, the researcher draws two conclusions: first, George Amberson Minafer copes his problem through changing his behaviour, from negative behavior to a positive one. He becomes more optimistic, independent and caring for his family. Second, George Amberson Minafer copes his problem through his actions. He has the courage to admit his mistake. He asks forgiveness to the man that he hurt most.